2020
DOI: 10.1016/j.heliyon.2020.e05399
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the hydraulic conductivity function of grey Vertosol with soil column test

Abstract: Expansive soils exhibit swell-shrink behaviour in wet-dry periods resulting in distresses on light-weight structures founded on/in them. Therefore, it is essential to investigate the climate-ground interaction when designing structures on expansive soils. Laboratory-based models are preferred to investigate the climatic-ground interaction of expansive soils due to the uncontrollability of the boundary conditions and expenses associated with field monitoring. More flexibility in analysing the climatic-induced h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Their results [5] confirmed that the slopes with an inclination less than 32 0 are theoretically stable even at extreme rainfall conditions. Further, it proved that a slope with a lesser saturated coefficient of permeability (i.e., less than 10 -6 m/s) and steeper slope inclinations up to 63 0 would not fail under shortterm extremely high rainfall intensities [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Their results [5] confirmed that the slopes with an inclination less than 32 0 are theoretically stable even at extreme rainfall conditions. Further, it proved that a slope with a lesser saturated coefficient of permeability (i.e., less than 10 -6 m/s) and steeper slope inclinations up to 63 0 would not fail under shortterm extremely high rainfall intensities [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Unsaturated soil behaviour and the soil properties are significantly dependent on the soil moisture conditions [1][2][3][4][5]. Therefore, it is imperative to identify accurate methods and instrument to investigate the moisture variations in soil profiles [1][2][3][4][5][6][7][8]. These investigations include laboratory-based element tests, model tests and field-based investigations.…”
Section: Introductionmentioning
confidence: 99%
“…These investigations include laboratory-based element tests, model tests and field-based investigations. The moisture sensitivity of expansive clays are considerably greater compared to non-reactive soils and hence, much attention has been given to these soils lately [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Geotechnical site investigation is of prime importance in ensuring the safety of civil engineering structures related to embankments, pavements and landfills [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Therefore the understanding of the soil interface shear strength is vital in designing and analysing the stability of geotechnical structures [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%